ANALISIS DUKUNGAN ORGANISASI TERHADAP PERILAKU KERJA INOVATIF GURU MA DI KECAMATAN TENJOLAYA BOGOR - Lestari, Hana; Indah Cahyaningrum, Siti; Rahmawati, Ima; Trimulyo, Joko (JURNAL KAJIAN ISLAM MODERN, 2025)
This research aims to determine the influence of organizational support on the innovative work behavior of MA teachers in Tenjolaya District, Bogor. This type of research is quantitative, with a survey method. The research subjects were 38 respondents taken using non-probability sampling techniques, namely saturated sampling, where the entire population was used as the research sample. Data was collected using a questionnaire containing answers determined by the researcher so that respondents could only choose one appropriate answer. The questionnaire in this study contains various positive and negative statements, with the measurement scale used in the questionnaire being a Likert scale with five alternative answers. The questionnaire for the innovative work behavior variable contains 40 items, and the questionnaire for the organizational support variable contains 42 items, which were tested for validity using a test Pearson product-moment and tested for reliability using Cronbach’s alpha, so that valid and reliable statement items were obtained for the innovative work behavior variable, namely 27 items, and the organizational support variable, namely 28 items. The data analysis technique is inferential statistics with a simple regression test assisted by SPSS version 26. To determine the influence of organizational support variables (X) on innovative work behavior (Y). The research results show an influence of organizational support on teachers’ innovative work behavior, with a significance value of 0,002 < 0,05. In addition, an R square value = 0,245, or equal to 24,5%, is obtained. So it can be interpreted that the organizational support variable (X) influences innovative work behavior (Y) by 24,5%. Therefore, to increase teachers’ innovative work behavior, it is hoped that each school can improve the provision of organizational support for teachers.